2019
DOI: 10.1161/strokeaha.118.023015
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Thrombi in the Cervico-Cephalic Arteries

Abstract: Background and Purpose— Intraluminal thrombus (ILT) is an uncommon finding among patients with ischemic stroke. We report clinical-imaging manifestations, treatment offered, and outcome among patients with ischemic stroke/transient ischemic attack and ILT in their cervico-cephalic arteries. Methods— Sixty-one of 3750 consecutive patients with acute ischemic stroke/transient ischemic attack (within 24 hours of onset) and ILT on initial arch-to-vertex com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 12 publications
3
66
1
Order By: Relevance
“…These were also termed intraluminal thrombus (ILT), intraluminal clot and were referred to as the doughnut sign [ 9 , 10 ]. Studies based on catheter angiography reported a prevalence of FFT ranging from 0.4% to 1.5% in patients with stroke or TIAs and with the recent utilization of CTA in those patients presenting acutely the prevalence has gone up to almost 3.2% [ 9 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These were also termed intraluminal thrombus (ILT), intraluminal clot and were referred to as the doughnut sign [ 9 , 10 ]. Studies based on catheter angiography reported a prevalence of FFT ranging from 0.4% to 1.5% in patients with stroke or TIAs and with the recent utilization of CTA in those patients presenting acutely the prevalence has gone up to almost 3.2% [ 9 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…FFT constitute a rare, but known, cause of cerebral ischemia. The prevalence of FFT is described at about 1.5% to 1.6% in stroke or transient ischemic attack (TIA) patients . Carotid artery ultrasonography is not only of importance for a first diagnosis, but furthermore provides an ideal monitoring method .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high short‐term morbidity and mortality, a therapeutic gold standard has not been established: There are several studies, including a recent prospective work and a meta‐analysis, as well as case reports on medical, surgical, and interventional approaches without a clear superiority regarding the clinical outcome. Inter alia, there are reports of different types of antiplatelet therapy including aspirin, clopidogrel, and ticlopidine, anticoagulation by either heparin, enoxaparin, dalteparin, or warfarin, off‐label uses of dabigatran or apixaban, surgical thrombectomy, and interventional stent‐retriever maneuvers (Table ). Based on the infrequency of description, none of these studies particularly addresses incidental findings but rather focus on symptomatic patients admitted to hospital for stroke or TIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Another important source of uncertainty was what to do in the presence of an intraluminal thrombus associated with the stenosis. 5 In a prospective cohort study involving 61 patients with acute stroke or transient ischemic attack and intraluminal thrombi in the cervicocephalic arteries, participants were variably treated with heparin (36%), clopidogrel (25%) or lowmolecular-weight heparin (23%).…”
mentioning
confidence: 99%